2015
DOI: 10.1016/j.chemosphere.2014.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Application of thermal desorption for the identification of mercury species in solids derived from coal utilization

Abstract: The speciation of mercury is currently attracting widespread interest because the emission, transport, deposition and behaviour of toxic mercury species depend on its chemical form. The identification of these species in low concentrations is no easy task and it is even more complex in coal combustion products due to the fact that these products contain organic and mineral matter that give rise to broad peaks and make it difficult to carry out qualitative and quantitative analysis. In this work, a solution to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 27 publications
1
46
0
Order By: Relevance
“…Also as shown in Table 1, it is reasonable to predicate that the mercury concentrations of surrounding soils will increase, if these two power plants continue to operate. The average mercury concentrations of soil samples collected 1 km away from Power Plant Baoji (606 μg/kg)33, Power Plant “A Horizon” (19,900 μg/kg)34, and Power Plant Chengdu (24,546 μg/kg)35 were much higher than those of Power Plants A (305 μg/kg) and B (383 μg/kg) in this research (Table 1). The main reason for this discrepancy should be that these three power plants have been operated for much longer than the two for this study.…”
Section: Resultsmentioning
confidence: 52%
“…Also as shown in Table 1, it is reasonable to predicate that the mercury concentrations of surrounding soils will increase, if these two power plants continue to operate. The average mercury concentrations of soil samples collected 1 km away from Power Plant Baoji (606 μg/kg)33, Power Plant “A Horizon” (19,900 μg/kg)34, and Power Plant Chengdu (24,546 μg/kg)35 were much higher than those of Power Plants A (305 μg/kg) and B (383 μg/kg) in this research (Table 1). The main reason for this discrepancy should be that these three power plants have been operated for much longer than the two for this study.…”
Section: Resultsmentioning
confidence: 52%
“…Discussion of the different mercury compounds identified in each type of sample (Table 3) is not a matter for this work and has already been described in previous studies carried out in HgTPD-1 by the authors [18,23]. Nevertheless, it is worth mentioning that in those studies red HgS and mercury bound to unburned particles (namely either Hg-OM or Hg-HA), were the main species present in the fly ashes.…”
Section: Mercury Species In Samples With a Low Carbon Contentmentioning
confidence: 83%
“…The fly ashes, namely CTL, CTA and CTP, were obtained from two pulverized coal power plants and a fluidized bed combustion plant, respectively. The characteristics of these fly ashes have been described elsewhere [18]. Two samples of gypsum (Gypsum A and Gypsum Z) were collected from the Wet Flue Gas Desulfuration Plants (WFGD) of two 1200 MW power stations.…”
Section: Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…The extensive work by Biester et al [10,35,[68][69][70][71] demonstrated the adaptation of an atomic absorption spectrometer, by means of an in-house apparatus consisting of an electronically controlled heating unit and a mercury detection unit [69]. An alternative method for mercury speciation by thermodesorption consists of the use of direct mercury analysers, such as the LECO ® AMA-254 [23,26] or Lumex ® RA-915 + PYRO-915 [72,73], by simply adjusting combustion temperature and the heating programme. Thermo-desorption methods present some advantages over conventional chemical extraction methods and x-ray absorption methods.…”
Section: Speciation By Thermo-desorptionmentioning
confidence: 99%